Ўйин орқали болалар монологик нутқини шакллантириш йўллари - Джолымбетова, М.М.; Гулмуратова, К. (SCIENCE and SOCIETY, 2023)
The problem of speech development of children of preschool agerast, speech defects and the formation of monologue speech in nix by means of games are presented in the state.